A self-healing and recyclable polyurethane/halloysite nanocomposite based on thermoreversible Diels-Alder reaction. (7th October 2020) - Lin, Changhong; Ge, Huan; Wang, Tianle; Huang, Min; Ying, Puyou; Zhang, Ping; Wu, Jianbo; Ren, Shibin; Levchenko, Vladimir
Abstract: The realization of recyclable materials is an urgent problem to be solved for extending practical applications in industry. Herein, a simple method was proposed to prepared the recyclable materials thorough dynamic reversible chemistry. In this work, we design the recyclable and self-healing polyurethane based on the thermoreversible dynamic Diels-Alder reaction. In addition, the Halloysite nanotubes (HNTs) were introduced into the system to improve the thermal properties, mechanical properties of polyurethane nanocomposites (PUDM/HNTs). The tensile tests showed that the HNTs can significantly improved the mechanical properties of nanocomposites. The healing efficiency above 90% on average was achieved which was determined by the recovery of breaking strength. Besides, the composites exhibited outstanding reprocessability via thermally induced. Therefore, Such excellent recyclable performance and self-healing ability give the polyurethane materials an opportunity to have great potential in the fields of save-energy, friendly-environment materials. Graphical abstract: Image 1 Highlights: The Polyurethane/HNTs nanocomposites show enhanced mechanical and thermal properties. The polyurethane materials have very high healing efficiency. The Polyurethane had good thermal self-healing and reprocessability behavior.